Optimization of Machining Time in Milling Process using Genetic Algorithm Method - abdullah, haslina; Isa, Norshafinaz (Research Progress in Mechanical and Manufacturing Engineering, 2023)
The machining time in the milling process is one of the mostimportant factors that affect the performance of machining in millingprocess. In this study, the genetic algorithm (GA) is being applied tooptimize the parameters such as depth of cut, feed per tooth, and cuttingspeed. In addition, this study also investigates the effect of the populationsizes, selection method, and reproduction options in Genetic AlgorithmToolbox (GAT) on machining times in milling processes using the GAmethod. In this study, the work piece of pocket milling develop by Solidworksoftware and the fitness function develop by Matlab software. Thepopulation sizes are being used in observing the effect towards theparameters and the most significantly is the machining time. Based on theresult obtained, the optimized machining time is 8.66007 minutes. Theoptimize value for depth of cut, feed per tooth and cutting speed are 1mm,0.127mm/tooth, and 30m/min, respectively were achieved together with theoptimize machining time. As a conclusion, Genetic Algorithm is capable tominimize the machining time by determine the optimum machiningparameters.